Descriptive profile of body structure of top Greco-Roman style wrestlers defined with method of multichannel bioelectric impedance - Kasum, G.; Dopsaj, M. (SportLogia, 2012)
Because of the specificity of given sport and weight categories wrestlers are characterized by specific morphologic characteristics. With the development of new measurement technologies there are some new opportunities for the development of new ways of obtaining information relevant to the sports system. One of the new technologies, which are used in area of measurement of body composition structure, is a method of bioimpedace, and the latest generations use a variant of the multichannel bioelectrical bioimpedance. The goal of this study is to define morphological model of top senior wrestlers by using the latest technological methods that will revalidate the existing knowledge about the given area. The sample of respondents is made of 22 male wrestlers, Greco-Roman style, top senior level athletes from four different countries: Serbia (n = 10), Croatia (n = 9), Montenegro (n = 2) and Greece (n = 1). Measurement of body composition is made with method of multichannel bioelectric impedance with professional apparatus of latest generation - InBody 720 Tetrapolar 8-Point Tactile Electrode System (Biospace, Co., Ltd). The most important result of this research is definition of generic (general) four-dimensional model (4D model) of body composition with quality international level wrestlers with following characteristics: in regards to average body mass of sample wrestlers - 81.95 kg, the amount of water is 55.08 L or 67.24 %, the amount of proteins is 15.00 kg or 18.33%, minerals 4.98 kg or 5.97% and fat mass 6.99 kg or 8.49 %.